2010
DOI: 10.1007/s10903-010-9355-3
|View full text |Cite
|
Sign up to set email alerts
|

Discharge of Infants from NICU to Latino Families with Limited English Proficiency

Abstract: Assess the needs of Latino families with limited English proficiency (LEP) whose infant is discharged from the NICU. Parent interviews at discharge and 1 month later. Thirty-six mothers were interviewed. Thirty nine percentage had <8th grade education; half earned <$10,000 annually. Twenty-eight percentage had no primary support person inside the US. Only half felt very prepared for their infants' discharge. Many expressed general worry about their infant's medical condition (53%) and development (81%), but fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 21 publications
1
43
1
1
Order By: Relevance
“…Although limited, similar findings have been reported in infants discharged from the NICU 16,22. However, this study found no association between maternal or infant demographic factors and errors.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although limited, similar findings have been reported in infants discharged from the NICU 16,22. However, this study found no association between maternal or infant demographic factors and errors.…”
Section: Discussionsupporting
confidence: 77%
“…If appointment errors had not been identified and addressed in a timely manner, infants might have missed valuable follow-up opportunities with the potential to prevent morbidities such as blindness, cerebral palsy, respiratory syncytial virus infection, neurodevelopmental delay, or failure to thrive 16. In addition, appropriate early follow-up can potentially prevent improper utilization of healthcare resources such as urgent care services and rehospitalization 17…”
Section: Discussionmentioning
confidence: 99%
“…Stress about apnea of prematurity and transitioning out of a highly monitored NICU environment was a common theme in studies of higher-SES NICU parents and lower-SES Latino families, indicating that these concerns are highly generalizable and should be a high priority for any NICU. 16,17,32,33 This anxiety about infants' readiness for discharge and feeling unprepared can have consequences that may go unrecognized by NICU providers. Parental unreadiness for NICU discharge is associated with suboptimal communication with outpatient providers.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these all depend on understanding the family’s circumstances through effective communication. Another issue may be that parents with NEPL are disinclined to ask for interpreters [28] and less likely to ask questions and participate in medical decision-making compared to English-speakers [29]. Normative cultural values such as simpatia (politeness and avoidance of confrontation) and respeto (importance of showing respect to authority figures) may contribute to lack of self-advocacy if parents perceive such behaviors may create conflict or show disrespect [27].…”
Section: Discussionmentioning
confidence: 99%